Ratio of Compressive Strength to Tensile Strength of Sea Sand and Sea Water Concrete With Propane Admixture - Muh Rizwan; Jasman; Adnan (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The need for concrete materials in construction is increasing, especially in coastal areas that often require concrete with special characteristics to deal with maritime environmental conditions; one of the challenges in development in the region is the limited availability of fresh water, so the use of seawater as an alternative in mixing concrete is a potential choice. In addition, abundant sea sand is also considered an economical fine aggregate material. The purpose of this study was to determine the effect of additives on the ratio of compressive strength and splitting tensile strength of concrete using sand and seawater as basic materials. This research method uses an experimental research method, namely by comparing normal concrete with Additive concrete to find out how the compressive strength and splitting tensile strength of concrete are. The results of the study showed that the compressive strength and splitting tensile strength test of normal concrete with additives, the results of the concrete compressive strength test at the age of 7 days increased by 16.84 Mpa, the age of 14 days by 8.93 Mpa, while the age of 28 days increased to 6.28 Mpa. In the splitting tensile strength test, concrete also experienced an increase at the age of 28 days by 0.400 MPa of normal concrete with an average of 22.64 MPa. So it can be concluded that concrete using additives reaches the planned compressive strength and splitting tensile strength and is suitable for use.